2022
DOI: 10.1002/micr.30946
|View full text |Cite
|
Sign up to set email alerts
|

Selection of deep or superficial recipient vein in lower extremity reconstruction using free flap: A systematic review and meta‐analysis

Abstract: Background: Free flap surgeries are useful procedures for lower-extremity reconstruction. Recipient vein selection for anastomosis is important to avoid venous congestion and thrombosis. Although deep or superficial venous system can be used as a recipient vein site, there is a lack of consensus on which system would be superior to avoid postoperative complications. This systematic review and meta-analysis aimed to assess the differences in outcomes between deep and superficial vein anastomosis for lower-extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Patient No. [13][14][15][16][17]. In these patients, DVT was discovered in the recipient veins of the ALTP flap in two patients and in the donor veins in three patients.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Patient No. [13][14][15][16][17]. In these patients, DVT was discovered in the recipient veins of the ALTP flap in two patients and in the donor veins in three patients.…”
Section: Resultsmentioning
confidence: 89%
“…However, most experienced surgeons recommended performing two venous anastomoses if possible ( 16 ). Furthermore, the incidence of thrombosis following venous anastomosis is generally lower in deep vein anastomosis than in superficial vein anastomosis ( 17 ). Therefore, one artery and two deep veins between the flap pedicle and the recipient vessel are usually connected in free tissue transfer to the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, superficial veins are used for anastomosis (Rodriguez Lorenzo et al, 2011). Meta‐analysis by Shimbo, Kawamoto, and Koshima (2022) concluded that the vascular thrombosis was significantly lower in deep veins when compared to superficial vein but had comparable rates of flap loss/necrosis. In our study irrespective of the number of veins or the system of veins used for anastomosis the results was not statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, superficial veins are used for anastomosis (Rodriguez Lorenzo et al, 2011). Meta-analysis by Shimbo, Kawamoto, and Koshima (2022) Successful outcome of the ALT free flap does not depend on the number of vein anastomosis or the system of vein anastomosis selected. However, large number of studies using superficial vein alone for anastomosis as first choice will prove their efficacy as a recipient vessel.…”
Section: Fiftymentioning
confidence: 99%
“…Contrary to patients whose main reason is the malignancy for reconstruction such as head and neck patients, the trauma (76.1%) (Shimbo et al, 2022) is the most important reason of lower extremity injuries. So, the operated group in lower extremity injuries is generally consist from productive ages as young and middle‐aged adults (Lee, Stranix, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%